The Role of Trust in Explaining Tourists' Behavioral Intention to Use E-booking Services in Taiwan. Issue 4 (2nd October 2019) - Jeng, Chi-Ruey
ABSTRACT: The tourism industry now allows the booking of rooms and itineraries via the internet; online bookings have become very important for both domestic and international businesses, leading to the emergence of online booking companies. This study has two research objectives: to identify the factors and their degree of influence on the intention to use e-booking services, and to identify the factors with the highest degree of influence on the intention to use e-booking among Taiwan users. We found that trust has a significant and positive relationship with perceived usefulness and ease of use. In turn, perceived usefulness positively influences intention to use and is positively related to behavioral intention to use information technology for travel; perceived ease of use positively relates to perceived usefulness; and behavioral intention positively influences the usage of information technology for travel. The empirical evidence from this study can be used to verify the importance of e-tourism and to support government efforts in developing the e-tourism platform and infrastructure.